(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
The STEM to STEAM movement has taken root over the past few years and is evolving as a positive action approach to truly meet the needs of the 21st century economy. STEM alone misses several key components that many employers, educators, and parents say are essential for our children to thrive now and in the rapidly approaching future.